PACE Technique to Error Categories: Its Effectiveness in Improving Word Problem Performance in Mathematics among the 7th Grade Students - Roghene A. Coloma; Florante P. Ibarra; Amirul Mukminin; Lenny Marzulina; Herri Mulyono; Kasinyo Harto (Qubahan Academic Journal)
This research determined the effectiveness of the PACE (Present the error, Analyze the error, Correct the Error, Explain the error) technique in improving the mathematics performance in solving word problems among 7th Grade students in Harnett Central Middle School, North Carolina, USA. The study utilized quasi-experimental research design with a validated researcher-made 7th Grade Mathematics test as the main instrument. The test was administered to 38 students before and after the implementation of the PACE technique. The data collected were treated using frequency counts, means, rates, Newman’s error analysis tool and t-test for dependent means. Before the implementation of the PACE technique, the students had a fair performance in solving word problems. In terms of their errors, transformation was the major error category in proportional relationships, reasoning about equations and inequalities and geometric and measurement reasoning; comprehension in reasoning with rational numbers, probabilistic reasoning and reasoning about population samples and comparing populations; and processing in reasoning about expressions. On the other hand, the students got an outstanding performance after the implementation of the PACE technique. After using the PACE technique, majority of the students had no errors in proportional relationships, reasoning with rational numbers, reasoning about expressions and reasoning about equations and inequalities; encoding errors in probabilistic reasoning and geometric and measurement reasoning; and transformation errors in reasoning about population samples and comparing populations. There was also a significant difference between the level of performance of students before and after using the PACE technique. Reading, comprehension, transformation and encoding are the error categories the PACE technique was most appropriate. And lastly, the PACE-Based 7th Grade Mathematics Workbook is very highly valid.